2017
DOI: 10.1200/jco.2017.35.15_suppl.8527
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with IBM Watson for Oncology (WFO) cognitive computing system for lung and colorectal cancer treatment.

Abstract: 8527 Background: IBM Watson for Oncology is an artificial intelligence cognitive computing system that provides confidence-ranked, evidence-based treatment recommendations for cancer. In the present study, we examine the level of agreement for lung and colorectal cancer therapy between the multidisciplinary tumour board from Manipal Comprehensive Cancer Centre in Bangalore, India, and Watson for Oncology. Methods: Watson for Oncology is a Memorial Sloan Kettering Cancer Center (New York, USA) trained cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This study showed that the overall concordance of WFO and the MDT was 54.5%. Although the concordance was lower than that in published studies on breast cancer [6], lung cancer [8], and advanced gastric cancer from South Korea [11], our finding is similar to the concordance of 49% in gastric cancer identified in a gastrointestinal cancer study reported at the 2017 American Society of Clinical Oncology (ASCO) Annual Meeting [10].…”
Section: Principal Findingssupporting
confidence: 69%
See 1 more Smart Citation
“…This study showed that the overall concordance of WFO and the MDT was 54.5%. Although the concordance was lower than that in published studies on breast cancer [6], lung cancer [8], and advanced gastric cancer from South Korea [11], our finding is similar to the concordance of 49% in gastric cancer identified in a gastrointestinal cancer study reported at the 2017 American Society of Clinical Oncology (ASCO) Annual Meeting [10].…”
Section: Principal Findingssupporting
confidence: 69%
“…There have been related reports on breast cancer [6][7][8], lung cancer [7][8][9], colorectal cancer [10], and other cancers, which have demonstrated high concordance between WFO and MDTs. However, research on gastric cancer has been limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…At present, Watson for Oncology has been applied in 14 countries worldwide, including China, the U.S., Holland, Thailand, India, Korea, Poland, Slovakia, and Bangladesh. In a double‐blind study involving 362 patients of Manipal Comprehensive Cancer Centre in India, treatment recommendations from WFO had a high degree of consistency with the Centres multidisciplinary tumor board .…”
Section: Introductionmentioning
confidence: 99%
“…“Cancer Drug Interactions” (https://cancer-druginteractions.org/), which is endorsed by the British Oncology Pharmacy Association, allows users to select from a list of anticancer drugs and commonly prescribed concomitant medications and obtain information on whether a DDI is likely, together with the rationale and quality of evidence. Watson for Oncology (https://www.ibm.com/watson/health/oncology-and-genomics/oncology/) is an artificial intelligence system that extracts data from medical records and provides evidence-based treatment options tailored to the individual patient 142,143. Lexicomp Online (http://www.lexi.com) and Micromedex 2.0 (http://micromedex.com) both include interactive tools for evaluation of drug interactions 144.…”
Section: Ddis: Aids For Clinical Decision-makingmentioning
confidence: 99%